As páginas de opinião dos jornais chineses e brasileiros : uma análise do jornal Zero Hora e do jornal Diário Yangcheng - Huang, Congyu (2012)
This research was made aimed investigating the chinese and brazilian newspapers and trying to find out the common points and differences in the layout and the contents of the opinion pages. We start with the analysis about the chinese jornalism theories, and some basic informations about the two newspapers. The agenda-setting hypothesis was focused in the studies of McCombs e Shaw, Mauro Wolff and Antonio Hohlfeldt, to verify a existence of the basic elements of agenda-setting in the two pages. We selected the Content Analysis and the Discourse Analysis as our methods for a quantitative and qualitative research, considering also the cultural, political and social influences. We analize the articles in the following aspects: the general informations, a layout of the page, editors and the sections, writers, topics, and the characteristics of the language